European integration deepening and widening: Implications for Asia - Rolf J. Langhammer (Kiel Institute of World Economics (IfW), 1998)
The paper discusses the relevance of past concerns about trade and foreign direct investment diversion to the detriment of Asian suppliers and hosts as a result of EU integration deepening and widening in the nineties. Based on recent empirical evidence, these concerns are rejected. As concerns integration deepening through the Single Market Program (SMP), trade resistance factors on the EU import side can be explained mainly by slow growth in Europe in the first half of the nineties rather than by SMP-induced trade barriers. Concerning integration widening toward Central and Eastern Europe (CEE), higher trade and investment shares of CEE are seen as a process of normalization which materialized earlier than the effects of the Europe Agreements. As trade overlaps between Asian and CEE supply on EU markets are low, the trade diversion fear is not well-founded. The paper also addresses the likely implications of the Single European Currency for Asia. Preliminary findings suggest that short-term implications are small but qualifications have to be made given the insufficient data base concerning the use of European currencies for invoicing, financial transactions, anchor and reserve purposes in Asia.
Keywords: F14; F15; 330; trade liberalization; foreign direct investment; monetary union; regional integration; EU-Binnenmarkt; EU-Erweiterung; Europäische Integration; Internationale Wirtschaftsbeziehungen; Direktinvestition; Asien; EU-Staaten; Europa